Pediatric otosyphilis—An unusual cause of conductive hearing loss - Zoya Arain, MBBS; Yasmin Abbas, MBChB MRCS(ENT); Ashok Adams, MRCP FRCR (Radiology Case Reports, 2020)
We present the case of a 5 year old female with a unilateral conductive hearing loss which had a relapsing and remitting course over a 3 year period. An initial noncontrast CT temporal bone study was unremarkable and a diagnosis of otitis media was made in the first instance. However, a second CT temporal bone study performed 3 years later demonstrated bilateral demineralisation of the ossicles and abnormal lucency affecting both the otic capsules. A diagnosis of otosyphilis was proposed on the basis of the imaging features and a prior medical history of previously treated congenital syphilis. With the benefit of hindsight, early pericochlear lucency was identified on the initial CT temporal bone study. There has been a steady rise of syphilis cases since the millennium with resurgence in many high income countries. Otosyphilis has a highly variable clinical presentation and there is limited data to establish the pattern of hearing loss in pediatric patients with a background of congenital otosyphilis. Temporal bone and otic capsule demineralisation carries a broad differential diagnosis including osteogenesis imperfecta, otosclerosis, Paget's disease and radiation related changes. Otosyphilis is a rare but potentially treatable cause of deafness and a high index of suspicion is required to make the diagnosis. In conjunction with a positive syphilis serology, a noncontrast temporal bone CT can aid the diagnosis and expedite the treatment. Keywords: Congenital, Juvenile, Otosyphilis, Pediatric